Prototipo para monitoreo de signos vitales enfocado a la atención de pacientes no hospitalizados en la ciudad de Iquitos 2021 - Romero Arcentales, Manuel Iván (2023)
This study was conducted in Iquitos city, whose purpose was to demonstrate the feasibility of using remote technology to obtain vital signs (heart rate, temperature and oxygen saturation) in contrast to current methods of obtaining vital signs by means of a prototype device, built based on Raspberry, arduino and sensors that allowed capturing the information of vital signs mentioned above.The research is quantitative, applied, Descriptive, with non-experimental transversal intervention with a tendency to case study with a single measurement. The study population consisted of all the records generated by the prototype to measure vital signs from July 15 to 26, the sample was non-probabilistic and was conducted through pilot tests where the indicators of precision and accuracy were recorded within the prototype variable, and for the monitoring variable, the time spent measuring temperature, SPo2 and heart rate was recorded. To determine whether the prototype was an accurate tool, the Gage R&R test with Minitab was used for each of the vital signs measured by the device, as well as the Linearity and Bias study to demonstrate that the prototype is an accurate measurement tool, and a SUS test was also carried out to calculate the degree of usability in terms of the appreciation of the medical personnel involved in the tests. The results of the experiment showed R&R values less than 20% and n > 6 which means that the tool was accurate, also P values > 0.05 and a bias within the tolerable range of measurement error according to the literature, the maximum tolerable error for the heart rate is 5bpm, temperature with 0. 5 C° and spo2 at 3%, demonstrating the accuracy of the prototype as a measurement tool, the SUS value was calculated with a total of 10 participants and the result was 83.25 out of 100 indicating that users rated our system as acceptable good.